Ten Tips for Increasing Wildlife Biodiversity in Your Pine Plantations - Holly K. Ober; Stanton Rosenthal; William Sheftall (EDIS, 2010)
WEC274, a 4-page fact sheet by Holly K. Ober, Stanton Rosenthal, and William Sheftall, discusses strategies forest landowners may adopt to provide habitat that will attract a diversity of wildlife species to their land. Includes additional sources of information. Published by the UF Department of Wildlife Ecology and Conservation, December 2009.